Plant growth promoting and antagonistic activity of bacillus strains isolated from rice rhizosphere - SUBHASIS MANDAL; PRAJESH DUTTA; SUKANTA MAJUMDAR (International Journal of Pharma and Bio Sciences, 2017)
Plant growth-promoting rhizobacteria (PGPR) are advantageous bacteria that inhabit around plant roots and enhance plant growth by a wide variety of direct and indirect mechanisms. Utilization of PGPR is now gradually increasing in agriculture and offers an attractive way to replace chemical fertilizers, pesticides, and supplements. In our present study six endospore forming bacterial isolates that were screened from rhizosphere of rice showed potential plant growth promoting (PGP) and antagonistic activities. Based on morphological and biochemical analyses the isolates were identified as Bacillus sp. Among the isolates (FB1-FB-6), all the strains produced IAA, FB3 produced siderophore and phytase. All the isolates produced lytic enzymes, and FB1-FB6 solubilized various sources of organic and inorganic phosphates as well as zinc. Strains FB1-FB6 also strongly inhibited the growth of several phytopathogens such as Macrophomina phaseolina, Fusarium oxysporum, Alternaria alternata and Colletotricum sp. in vitro. Since, Bacillus sp. FB1-FB6 shows PGP and antifungal activities so it can be surmised that the isolated strains have strong potential to be successful biofertilizers and bioenhacers.